Gaya Arsitektur Yunani Kuno dan Pengaruhnya Terhadap Seni Bangunan Di Indonesia - Joko Budiwiyanto (Ornamen, 2008)
This article represent result of bibliography study to Ancient Greek architecture style and its influence to techtonics in Indonesia. Greek Architecture represent the architecture with the characteristic of pillar. Architecture of Greek pillar is basically consisted of three style, that is Doria, Ionia and Korinthia. Ancient Greek Architecture with the characteristic of its pillar style try traced its influence to techtonics in Indonesia.Keyword: Arsitektur Yunani Kuno, Gaya Doria, Ionia, Korinthia.